Analisis Pemanfaatan Pelayanan Kesehatan di Puskesmas Dempar Kecamatan Nyuatan Kabupaten Kutai Barat - Deby Eunike Lestari; Iwan M. Ramdan; Andi Anwar (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2019)
Low of visit number in Health service utilization is affected by many factors. Influencing faktors are health service user and service provider. This research aimes to know social structural factor, health belief and health assessment correlates wit health service utilization in Puskesmas Dempar. This quantitative research uses analytic survery with cross sectional approach that is done on August – September in 2018, sampling technique used a random sampling method with 299 respondents in the working area of the Dempar Health Center. Primary data collection methods (questionnaires and interviews). The statistical test used is the Chi Square test. Research result shows that on dependent variable 88.3% respondents utilized health service well, and after it is tested the correlation with independent variable is there were correlations between health assessment variable with health service utilization with significant value (p=0,004), whereas variable there are no correlations between social structure (p=0,497) and health belief (p=0,844) toward health service usage in Puskesmas Dempar. It is suggested for Puskesmas Dempar to makes knowledge improvement and attitude change through counselling about disease along with health program socialization, health officer to approach society, also by improving service well.